2006
DOI: 10.1165/rcmb.2005-0223oc
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxia-Induced Reactive Oxygen Species Formation in Pulmonary Capillary Endothelial Cells In Situ

Abstract: Lung capillary endothelial cells (ECs) are a critical target of oxygen toxicity and play a central role in the pathogenesis of hyperoxic lung injury. To determine mechanisms and time course of EC activation in normobaric hyperoxia, we measured endothelial concentration of reactive oxygen species (ROS) and cytosolic calcium ([Ca(2+)](i)) by in situ imaging of 2',7'-dichlorofluorescein (DCF) and fura 2 fluorescence, respectively, and translocation of the small GTPase Rac1 by immunofluorescence in isolated perfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
159
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 185 publications
(165 citation statements)
references
References 60 publications
5
159
1
Order By: Relevance
“…Sheep pulmonary microvascular EC exposure to hyperoxia (100% O 2 , 30 min) increased the cellular O 2 ⅐ Ϫ production, as detected by EPR spectroscopy, and blocking the ETC with rotenone decreased the O 2 ⅐ Ϫ signal (67). Detection of ROS in capillary ECs by in situ imaging of 2Ј,7Ј-dichlorofluorescein fluorescence in perfused rat lungs showed that ROS formation increases with PO 2 (21-100% O 2 , 90 min) and originates from mitochondria (9).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Sheep pulmonary microvascular EC exposure to hyperoxia (100% O 2 , 30 min) increased the cellular O 2 ⅐ Ϫ production, as detected by EPR spectroscopy, and blocking the ETC with rotenone decreased the O 2 ⅐ Ϫ signal (67). Detection of ROS in capillary ECs by in situ imaging of 2Ј,7Ј-dichlorofluorescein fluorescence in perfused rat lungs showed that ROS formation increases with PO 2 (21-100% O 2 , 90 min) and originates from mitochondria (9).…”
Section: Discussionmentioning
confidence: 95%
“…Since it is known that 1-4% of O 2 reacting with the ETC is incompletely reduced to O 2 ⅐ Ϫ , and the O 2 ⅐ Ϫ formation rate by the ETC complexes III and I increases linearly with O 2 concentration (42,74), we hypothesized that, under flow, the relative "hyperoxic state" of 21% O 2 raises the O 2 concentration in EC mitochondria and enhances the formation of O 2 ⅐ Ϫ , which, via the reaction with shear-induced NO, increases the intramitochondrial ONOO Ϫ levels and potentiates the inhibition of respiration. Although it is known that 1) either hyperoxia (21-100% O 2 ) or H (1-3% O 2 )/RO (21% O 2 ) increases the mitochondrial O 2 ⅐ Ϫ generation and inhibits respiration (9,21,33,67,71) and 2) shear at 21% O 2 increases the EC ONOO Ϫ formation intramitochondrially (30), the respiratory function of sheared ECs at 21% O 2 and at lower, but physiological, O 2 levels has not been examined.…”
mentioning
confidence: 99%
“…Experimental procedures have been described previously (7,48). For isolated perfusion, lungs from anesthetized Sprague-Dawley rats were continuously pump-perfused at 14 ml/min and 37°C.…”
Section: Animalsmentioning
confidence: 99%
“…We considered the hypothesis that by increasing the level of ambient ROIs, hyperoxia may attenuate the excessive inflammation and injury observed in CGD mice following acid injury. Hyperoxia may also increase the level of NADPH oxidase-derived ROIs from lung endothelial cells (2,30). The effect of hyperoxia is to increase ambient levels of ROIs, whereas activation of the NADPH oxidase in phagocytes results in a rapid burst of superoxide anion generation and downstream ROI metabolites.…”
Section: Ajp-lung Cell Mol Physiolmentioning
confidence: 99%